Estimationing Residential Water Use Gap in the Privileged Provinces: Spatial Panel Approach - mohammadreza Monjazeb; Aida Gaseminejad (پژوهشهای اقتصادی, 2020)
The optimization of water use will be an important issue for Iran in the coming years.  In this paper, the gap between current and optimal water use has been estimated using Spatial Durbin Model (SDM), as special case of Spatial Panel Data, for 18 selected provinces during 2003-2015.  Notable characteristic of this model in comparison with other spatial models (including SEM and SAR) is to enter spatial lags of dependent and explanatory variables in the model simultaneously. This model has been selected by Wald Test. Results show that population and income have positive effects on residential water consumption, but water tariff has negative impact on domestic water use. According to the findings, water tariff can be applied as an instrument for controlling the level of water consumption. Especially in high-consumption provinces, water pricing can be more effective in reducing water use.